PENANAMAN NILAI RELIGIUS SEBAGAI PENGUATAN KARAKTER SISWA MELALUI PEMBELAJARAN AQIDAH AKHLAK DI MIN 3 WAY KANAN - Andrean, Seka; Devi, Aulia Diana (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2020)
Madrasah Ibtidaiyah is an educational institution that has a strategic role in embedding religious values early on in students. In everyday life religious value is a character value that affects the choice of the way or the purpose of action from several alternatives and leads to behavior and satisfaction. In the face of the disruption era and the moral degradation as it is today, this religious character is indispensable for students to perform praiseworthy morality and to avoid unblemish morality. The focus of this research is to describe the model of religious character planting in Madrasah and teacher learning planning of Aqidah Akhlak as an effort to planting the character of religious students at MIN 3 Way Kanan . Data collection is done by observation, interviews, and documentation. The analysis of data in qualitative research is inductive i.e. withdrawal of sympulsion is common from the field data. The results show the religious values instilled in MIN 3 Way Kanan covers the value of discipline, honesty, responsibility, sincerity, tolerance, mutual respect, and caring for the environment.